Management of patients with Cushing’s disease in the Gulf Region: a Delphi consensus recommendation - Almalki, Mussa H.; Elhadd, Tarik; AlDahmani, Khaled M.; Ekhzaimy, Aishah; Alqanaei, Abdullah; Jamal, Hasan F.; Alfutaisi, Abdulla; Mahzari, Moeber; Beshyah, Salem A.; Alzahrani, Ali S. (Frontiers in Endocrinology, 2025)
IntroductionCushing’s disease (CD), most commonly caused by ACTH-secreting pituitary adenomas, is a rare but serious endocrine disorder characterized by chronic hypercortisolism. CD is associated with significant morbidity and increased mortality, necessitating timely and effective intervention.ObjectivesThis study aimed to establish consensus-based clinical practice guidelines for managing CD in the Arabian Gulf region, where disparities in healthcare infrastructure and access to therapies present challenges to optimal care delivery.MethodsA Delphi consensus approach was employed, involving 83 endocrinologists with ≥5 years of independent practice from the six Gulf Cooperation Council (GCC) countries. A scientific committee developed 21 statements covering surgical, medical, and radiotherapeutic management. Consensus was predefined as ≥80% agreement on a 5-point Likert scale.ResultsThe Delphi survey revealed strong expert consensus on CD management: nearly all agreed on referral to specialized centers (98.8%) and endorsed transsphenoidal surgery (100%) as first-line treatment. For persistent/recurrent disease, repeat surgery was favored when feasible (91.3%), while medical therapy (e.g., pasireotide or steroidogenesis inhibitors) was preferred for inoperable cases. Drug choice depended on clinical context, with radiotherapy (98.8%) reserved for refractory cases and bilateral adrenalectomy (95.2%) as a last resort. Monitoring protocols, including glycemic and adrenal function assessments, achieved high agreement (97.6–100%).ConclusionThe study provides structured, region-specific recommendations for CD management in the Gulf region, emphasizing surgical intervention where feasible, tailored medical therapy, and careful monitoring. These guidelines aim to standardize care, address resource limitations, and improve patient outcomes.